Changes in breakfast and water consumption among adolescents in Canada: examining the impact of COVID-19 in worsening inequity - Duncan, Markus J.; Belita, Emily; Amores, Angelica; Riazi, Negin A.; Carsley, Sarah; Vanderloo, Leigh M.; Carson, Valerie; Chaput, Jean-Philippe; Faulkner, Guy; Leatherdale, Scott T.; Patte, Karen A. (Université d'Ottawa | University of Ottawa, 2024)
Abstract Background To assess whether changes in breakfast and water consumption during the first full school year after the emergence of the COVID-19 pandemic varied based on sex/gender, race/ethnicity, and socioeconomic status among Canadian adolescents. Methods Prospective annual survey data collected pre- (October 2019-March 2020) and post-COVID-19 onset (November 2020-June 2021) the Cannabis, Obesity, Mental health, Physical activity, Alcohol, Smoking, and Sedentary behaviour (COMPASS) study. The sample consisted of 8,128 students; mean (SD) age = 14.2 (1.3) years from a convenience sample of 41 Canadian secondary schools. At both timepoints self-reported breakfast and water consumption were dichotomized as daily or not. Multivariable logistic generalized estimating equations with school clustering were used to estimate differences in maintenance/adoption of daily consumption post-COVID-19 based on demographic factors, while controlling for pre-COVID-19 behaviour. Results Adjusted odds ratios (AOR) with 95% confidence intervals are reported. Females (AOR = 0.71 [0.63, 0.79]) and lower socioeconomic status individuals (AORLowest:Highest=0.41 [0.16, 1.00]) were less likely to maintain/adopt daily breakfast consumption than male and higher socioeconomic status peers in the 2020–2021 school year. Black identifying individuals were less likely than all other racial/ethnic identities to maintain/adopt plain water consumption every day of the week (AOR = 0.33 [0.15, 0.75], p < 0.001). No significant interaction effects were detected. Conclusions Results support the hypothesis that changes in nutritional behaviours were not equal across demographic groups. Female, lower socioeconomic status, and Black adolescents reported greater declines in healthy nutritional behaviours. Public health interventions to improve adherence to daily breakfast and water consumption should target these segments of the population. Trial Registration Not a trial.